SAT0471 Autologous Hematopoietic Stem Cell Transplantation in Rapidly Progressive Systemic Sclerosis is More Effective Than Conventional Therapies in Inducing Disease Remission and Prologing Survival. (9th June 2015) - Del Papa, N.; Zaccara, E.; Maglione, W.; Sambataro, D.; Sambataro, G.; Andracco, R.; Saporiti, G.; Giordano, R.; Vitali, C.; Cortelezzi, A.; Onida, F.
Abstract : Background: Autologous haematopoietic stem cell transplantation (AHSCT) has shown to be an effective therapeutic option to prolong survival of patients (pts) suffering from rapidly progressive diffuse cutaneous systemic sclerosis (rp-dcSSc). Objectives: This study was aimed at retrospectively comparing the disease outcome of pts with rp-dcSSc treated with AHSCT to that of age-, and sex-matched group of clinically similar pts selected from our cohort and treated with conventional therapies. Methods: Eighteen pts (5 M, 13F; median age 40, 20-62 yrs) that underwent AHSCT were compared to 36 age- and sex-matched pts (10 M, 26 F; median age 44, 19-62 yrs), all of them suffering from rp-dcSSc. At the starting evaluation point the two groups were also exactly comparable for disease-duration and clinical findings, in term of skin involvement (mRSS), DLCO as % of predicted value and disease activity (ESSG scoring system). AHSCT was performed by mobilisation with cyclophosphamide (CTX) and G-CSF, selection of CD34+ cells and conditioning regimen with CTX and rabbit ATG. Twenty-five pts in the control group received 6 monthly pulses of intravenous CTX (750mg/m 2 ), 11 received steroids, DMARDS (Methotrexate and Azathioprine) and vasoactive therapies (noCTX). The clinical course in AHSCT and control groups was evaluated from time 0 to 5 years by using Kaplan Meyer survival curves, computing the Hazard Ratio (HR) and Chi square distribution. Results: Results of the survival curve analysis of different groups, expressed as HR (95%CI) are reported in the table . Conclusions: This retrospective study confirms that AHSCT approach is more effective to induce a longer survival (p=0.0004), and shows that is also able to more rapidly reduce the mRss (p<0.0001), disease activity (p<0.0001), and preserve lung function (p=0.0004), with respect to conventional therapies in rp-dcSSc. Disclosure of Interest: None declared